Model predictive control using Euler method for switched-battery boost-multilevel inverter - Ahmad Takiyuddin Abdullah; Sevia Mahdaliza Idrus; Shahrin Md Ayob (Institute of Advanced Engineering and Science, 2023)
This paper presents the model predictive control (MPC) design using the backward Euler method for an 11-level switched-battery boost multilevel inverter (SBBMLI). The SBBMLI was proposed as the cost-effective solution for the communication power line in a high-speed rail (HSR) system. Initially, a generalized SBBMLI problem formulation was performed, and an open-loop simulation based on voltage and current mode controls was conducted. The finite control set-model predictive control (FCS-MPC) ability to track the reference sinusoidal output with low total harmonic distortion (THD)Â was then assessed as a performance criterion. Furthermore, the performance was assessed based on no-load and load disturbances. Finally, the results proved the ability of the proposed FCS-MPC to address non-linear dynamics, constraints, and its eï¬ƒciency of implementation.